1998
DOI: 10.1128/mcb.18.5.2892
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Regulation of bicoid mRNA Stability Is Mediated by the First 43 Nucleotides of the 3′ Untranslated Region

Abstract: During the transition from the maternal to the zygotic developmental program, the expression of genes important for pattern formation or cell cycle regulation changes dramatically. Rapid changes in gene expression are achieved in part through the control of mRNA stability. This report focuses on bicoid, a gene essential for formation of anterior embryonic structures in Drosophila melanogaster. bicoid mRNA is synthesized exclusively during oogenesis. Here, we show that bicoid mRNA stability is regulated. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
49
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 35 publications
10
49
0
Order By: Relevance
“…3H,I). Before nuclear cycle 14, bcd mRNA must be stable because little, if any, degradation was apparent, as previously observed in activated unfertilized eggs (Surdej and Jacobs-Lorena, 1998). …”
Section: Analysis By Fish and Confocal Microscopy Of Bcd Mrna Gradiensupporting
confidence: 58%
See 1 more Smart Citation
“…3H,I). Before nuclear cycle 14, bcd mRNA must be stable because little, if any, degradation was apparent, as previously observed in activated unfertilized eggs (Surdej and Jacobs-Lorena, 1998). …”
Section: Analysis By Fish and Confocal Microscopy Of Bcd Mrna Gradiensupporting
confidence: 58%
“…Therefore, bcd mRNA is degraded in the basal and apical periplasm, or only in the latter. This degradation is presumably mediated by a bcd instability element (BIE) located within a 43-nucleotide sequence following the stop codon (Surdej and Jacobs-Lorena, 1998). In mammals, Stau may trigger the degradation of an mRNA by binding to its 3ЈUTR and to the nonsense-mediated decay (NMD) factor Upf1, in a process that is different from NMD and is called Staufenmediated mRNA decay (SMD) (Kim et al, 2005).…”
Section: Is Degradation Of Bcd Mrna Also Mediated By Stau?mentioning
confidence: 99%
“…A possible contribution of the 11 nt 5ЈUTR, which was the only other CWP1-derived sequence in the mRNA tested, will have to be examined. Modulation of mRNA stability via cis motifs in the 3ЈUTR appears to be ubiquitous in cells that undergo differentiation and has been described in protozoa (Vanhamme and Pays, 1995), Drosophila (Surdej and Jacobs-Lorena, 1998), mammals (Mitchusson et al, 1998), and other organisms. Particularly in protozoa, the sequence motifs responsible for interaction with putative trans-acting factors that influence mRNA instability have been difficult to pin down, because multiple and sometimes widely spaced regions are involved and consensus motifs are very degenerate Schurch et al, 1997;Wilson et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…bcd) degradation pathways; and those targeted by both (e.g. Hsp83) (Bashirullah et al, 1999;Surdej and Jacobs-Lorena, 1998). (B) In the mouse, genomic profiling (Hamatani et al, 2004) has revealed clusters of maternal transcripts that appear to degrade with kinetics that correspond to the subsets identified in D. melanogaster: Clusters 3 and 9 degrade in the absence of significant zygotic transcription; degradation of cluster 7 transcripts appears to accelerate coincident with the onset of the major zygotic genome activation (ZGA) wave, whereas cluster 6b transcripts most resemble the stable subset.…”
Section: Mechanisms Of Maternal Transcript Destabilizationmentioning
confidence: 99%